2022
DOI: 10.1155/2022/6358707
|View full text |Cite
|
Sign up to set email alerts
|

Survival Analysis and a Novel Nomogram Model for Progression-Free Survival in Patients with Prostate Cancer

Abstract: Background. This study sought to perform a survival analysis and construct a prognostic nomogram model based on the Gleason grade, total prostate-specific antigen (tPSA), alkaline phosphate (ALP), and TNM stage in patients with prostate cancer (PCa). Methods. The progression-free survival (PFS) of 255 PCa patients was analyzed in this study. The prognostic value of tPSA and ALP was evaluated using the Kaplan-Meier survival curves and Cox regression analysis, and a nomogram model based on the Gleason grade, tPS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Nomograms, a statistic-based tool, can assess the risk of clinicopathological features by quantifying the biological and clinical variables of patients with cancer (6). To date, nomograms have been widely applied in the personalized prediction of cancer, such lung, cervical, prostate, and hepatocellular carcinomas (7)(8)(9)(10)(11). To the best of our knowledge, several studies have reported risk factors associated with breast cancer (12)(13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…Nomograms, a statistic-based tool, can assess the risk of clinicopathological features by quantifying the biological and clinical variables of patients with cancer (6). To date, nomograms have been widely applied in the personalized prediction of cancer, such lung, cervical, prostate, and hepatocellular carcinomas (7)(8)(9)(10)(11). To the best of our knowledge, several studies have reported risk factors associated with breast cancer (12)(13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…Hu et al developed a prognostic prediction model based on 22 autophagy-related genes expressed in PC patients ( 11 ). Han et al conducted a prognostic nomogram for progression-free survival of 255 PC patients ( 12 ). However, the clinical applicability of these models is limited by the need to collect clinical samples and predictive ability.…”
Section: Introductionmentioning
confidence: 99%